2020
DOI: 10.3389/fonc.2020.531131
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Related Cytotoxically Active CD8+ TIL Are Inversely Associated With Lung Cancer Development

Abstract: Lung cancer is the most common cancer type around the world. Although major advances in cancer therapy, lung cancer has been the largest proportion of all cancer-related deaths. The respiratory tract contains many types of bacteria and a distinct lung microbiome in lung cancer patients was described in many studies. The specific roles of these lung microorganisms in lung cancer progression remain unclear. In this study, we evaluated the effect of inhalation of bronchoalveolar fluid (BAL) in the lung cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, CD8+ T cells are considered an important barrier to the long-term survival of organ allografts [ 34 , 35 ]. A previous study showed a strong positive relationship between Pasteurella and the infiltration of CD8+ T cells in patients with lung cancer [ 36 ]. However, in this study, we were unable to confirm the relationship between specific bacteria and CD8+ T cells due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD8+ T cells are considered an important barrier to the long-term survival of organ allografts [ 34 , 35 ]. A previous study showed a strong positive relationship between Pasteurella and the infiltration of CD8+ T cells in patients with lung cancer [ 36 ]. However, in this study, we were unable to confirm the relationship between specific bacteria and CD8+ T cells due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study revealed that Pasteurella has a positive correlation with cytotoxic CD8+ TILs and a negative correlation with M2 macrophages. There is a significant positive correlation between Coriobacteriaceae and M2 macrophages and a negative correlation with CD8+ cells [60]. Together, these immune reactions affect the occurrence and development of lung tumors.…”
Section: Immunitymentioning
confidence: 98%
“…All these immune responses influence the initiation and development of lung tumours. 201 Certain microorganisms, such as Staphylococcus aureus , HBV, and HCV, potentially promote the progression of prostate and liver cancers by promoting the immunosuppression mediated by T regulatory cells (Tregs). 202 204 Moreover, a large number of Tregs have been observed in HPV-induced cervical lesions, and the level of Tregs is associated with the severity of the disease, suggesting that Tregs may be involved in the interference of anti-HPV immune response.…”
Section: Role Of Intratumoural Microbiota In the Development Of Cancermentioning
confidence: 99%